2013
DOI: 10.1200/jco.2013.31.18_suppl.lba2009
|View full text |Cite
|
Sign up to set email alerts
|

Cilengitide combined with standard treatment for patients with newly diagnosed glioblastoma and methylated O6-methylguanine-DNA methyltransferase (MGMT) gene promoter: Key results of the multicenter, randomized, open-label, controlled, phase III CENTRIC study.

Abstract: LBA2009 Background: Cilengitide (CIL) is a selective αvβ3 and αvβ5 integrin inhibitor. In a phase II study in patients with newly diagnosed glioblastoma, CIL added to standard temozolomide (TMZ) and radiotherapy (RT) was well tolerated and appeared to confer improved survival in patients with glioblastoma and methylated MGMT gene promoter (Stupp et al. J Clin Oncol. 2010;28:2712-8). Methods: This multicenter, randomized, controlled, open-label, phase III study randomized (1:1) patients (≥ 18 years) with newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…Sim ilarly, a difference of 2.8 months between in vestigator and independent-review assessments was observed in the CENTRIC trial (Cilengitide in Combination with Temozolomide and Radiotherapy in Newly Diagnosed Glioblastoma Phase III Randomized Clinical Trial; ClinicalTrials.gov number, NCT00689221) of cilengitide plus radiotherapy-temozolomide for newly diagnosed glioblastoma. 33 The adapted Macdonald Response Criteria, which were used to assess progression, anticipated some of the key features of the Response Assessment in Neuro-Oncology (RANO) Working Group criteria, which were not available at the time of the initiation of our study. 25,26 The adapted Macdonald Response Criteria addressed the observed limitations of imaging assessment by including qualitative evaluation of both noncontrast-enhancing components (by means of T 2 -weighted imaging or fluid-attenuated inversion recovery [FLAIR]) and small contrastenhancing lesions (at least one diameter <10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Sim ilarly, a difference of 2.8 months between in vestigator and independent-review assessments was observed in the CENTRIC trial (Cilengitide in Combination with Temozolomide and Radiotherapy in Newly Diagnosed Glioblastoma Phase III Randomized Clinical Trial; ClinicalTrials.gov number, NCT00689221) of cilengitide plus radiotherapy-temozolomide for newly diagnosed glioblastoma. 33 The adapted Macdonald Response Criteria, which were used to assess progression, anticipated some of the key features of the Response Assessment in Neuro-Oncology (RANO) Working Group criteria, which were not available at the time of the initiation of our study. 25,26 The adapted Macdonald Response Criteria addressed the observed limitations of imaging assessment by including qualitative evaluation of both noncontrast-enhancing components (by means of T 2 -weighted imaging or fluid-attenuated inversion recovery [FLAIR]) and small contrastenhancing lesions (at least one diameter <10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…From the academic and caregivers perspective, however, it will be difficult to European randomized controlled phase II study, which completed accrual in 2012, will become available in 2014 [16]. The CORE study is a formal companion to the CENTRIC trial, in which the integrin inhibitor cilengitide was added to (not replacing) radiochemotherapy with TMZ in MGMT-unmethylated glioblastoma patients [14]. In this study, radiochemotherapy with TMZ was compared with radiochemotherapy with TMZ plus cilengitide at two different dosing schedules in a randomized phase II three-arm design.…”
Section: Targeted Therapies In Patients With Mgmt Promoter-unmethylatmentioning
confidence: 99%
“…Due to its high prognostic and predictive relevance, assessment of the MGMT status has become state-of-the-art in current and planned clinical trials in glioma as a prognosticator and to stratify patients [9] or even patient selection into trials accordingly [14][15][16][17]. In addition, it is nowadays frequently requested in routine diagnostics as a prognostic tool.…”
Section: Targeted Therapies In Patients With Mgmt Promoter-unmethylatmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that no change in the patterns of progression in a cohort of cilengitide-treated patients compared to a cohort of patients from the experimental arm of the EORTC 26981/22981 NCIC CE.3 was observed is reassuring. The major limitation of the present study is the small sample size and the uncertainty of its relevance in the future: preliminary results from the subsequently performed phase 3 trial, CENTRIC, indicate that the primary endpoint of prolonging overall survival was not reached [13]. Yet, our analysis serves as a baseline and reference for the future study of the role of modulation of integrins in the treatment of newly diagnosed glioblastoma.…”
Section: Resultsmentioning
confidence: 99%